La migración de los indígenas de Oaxaca, México, a Estados Unidos y su movilización social - Barabas Reyna, Alicia Mabel (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
The paper is a general view of transnational indigenous migration between Oaxaca in México to California. I’m concerned in three aspects: a) the frontier and the territoriality of migrants, b) the transnational communities and social mobilization and, c) the re-configuration of migrant’s cultures and the new dimensions of ethnic identity in migration contexts.